How does buoyancy affect performance during a 200m maximum front crawl swim? - Psycharakis, S. G.; Yanai, T. (Journal of Sports Sciences, 2018)
We investigated the rotational effect of buoyant force around the body`s transverse axis, termed buoyant torque, during a 200m front crawl maximal swim. Eleven male swimmers of national or international level participated. One stroke cycle (SC) for each 50m was recorded with two above and four below water cameras. The following variables were analysed: swimming velocity; absolute and normalised buoyant force; minimum, average and maximum buoyant torque; SC and arm recovery times. The average value of buoyant torque was higher in the first 50m (14.2 ± 4.5Nm) than in the following 150m (9.3 ± 4.1Nm~10.9 ± 4.5Nm) and was directed to raise the legs and lower the head throughout the race. The change in its magnitude seemed to be linked to the shorter time spent proportionally in arm recovery (first 50m: 27.6% of SC time; next 150m: 23.3-24.4% of SC time). Most swimmers had periods of the SC where buoyant torque was directed to sink the legs, which accounted to 10% of SC time in the first 50m and about twice this duration in the next 150m. These periods were observed exclusively at some instances when the recovering arm had entered the water while the opposite arm was still underwater.